EFL STUDENTS’ EXPERIENCE WITH AI TOOLS USED IN THEIR EFL LEARNING - Herusatoto, Hesthi; Rini, Sri Endah Setia (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2024)
This research investigated English as a Foreign Language (EFL) students’ familiarity with AI tools, the frequency of use, the purpose of use, and the perceived benefits of the tools in EFL learning. Undergraduate and Diploma 3 students batch 2020-2023 of a private English language college in Yogyakarta, Indonesia were asked to respond to a questionnaire surveying AI tools they are using in their EFL learning and the applications. Among the 34 AI tools mentioned in the questionnaire, Google Translate, Chat GPT, Grammarly, Canva, Quizziz, and Voice Generator were the most frequently used by the majority of the respondents. The respondents reported using AI tools in their EFL learning sometimes rather than always. Most of them sometimes used the tools for brainstorming, writing support, personalized and immediate English learning support, searching research references, analysis support, multi-media support, and audio support. The majority, however, reported never using the tools for audio multi-media support. Overall, a significant number respondents reported that AI Tools is beneficial because it helps them learn English, enhance their depth of thinking and understanding, and improve their grammar. As for generations, generation Z generally used AI tools to generate ideas, writing support, analysis support, and visual multi-media support. The Millennial often used AI for personalized and immediate English learning, searching research references, and audio multi-media support. In addition, the respondents greatly benefited from AI as AI helped improve their English skills, depth of thinking and understanding, and grammatical skills.